Inflammatory cytokines and alpha-fetoprotein concentrations for predicting survival in patients with hepatocellular carcinoma - Han, Xue; Gu, Yangkui; Li, Shaolong; Chen, Minshan; Cai, Qingqing; Huang, Jinhua (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Chronic inflammation is crucial in the evolution of hepatocellular carcinoma (HCC). Circulatory and intratumoral inflammatory factors are always increased in these patients. In this study, we determined the value of pretherapy serum concentrations of several inflammatory cytokines for predicting survival among patients with HCC. Methods: We retrospectively analyzed data of 85 patients with HCC with known alpha-fetoprotein (AFP) concentrations diagnosed at our institute. Before therapy, serum concentrations of interleukin (IL)-2, -4, -6, -10, interferon gamma, and tumor necrosis factor alpha were measured by flow cytometry. Correlations between these serum factors and clinical parameters were tested. Statistical analysis was made by using non-parametric procedures and survival analysis. The expression of IL-6 and the co-expression of IL-6 and CD11b, marker of myeloid cell in HCC tumor tissues, were evaluated by immunohistochemistry and immunofluorescence, respectively. Results: The only independent predictor of overall survival (OS) was IL-6 [hazard ratio (HR), 3.338; 95% CI, 1.671 to 6.666; P=0.001]. OS was shorter among patients with high concentrations of both IL-6 (≥1.435 pg/mL) and AFP (≥400 ng/mL) than it was in those with high concentrations of either IL-6 or AFP; survival was significantly longer in patients with low concentrations of both markers (P